2023
DOI: 10.3389/frph.2023.1144217
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of the dual prevention pill for contraception and HIV pre-exposure prophylaxis

Abstract: IntroductionWomen in sub-Saharan Africa (SSA) experience the world's highest rates of both HIV infection and unintended pregnancy. The Dual Prevention Pill (DPP) is a novel multipurpose prevention technology (MPT) that co-formulates HIV pre-exposure prophylaxis (PrEP) and combined hormonal oral contraception into a single daily pill. As a dual indication product, the DPP may be preferred by women facing these overlapping health risks. However, most SSA countries face severe healthcare resource constraints. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In both scenarios above–either attracting new users or expanding coverage to those with unmet need for a second indication–additional benefit is realized so long as the added coverage occurs among women at high risk for the outcomes as suggested by cost effectiveness modeling. Analyses scaling a MPT for HIV and pregnancy found pregnancy prevention would be cost effective if rolled out to women at high risk of HIV (e.g., serodiscordant couples, AGYW or female sex workers) but not to a general population of women ( 14 , 15 ). Notable was that a MPT for HIV and pregnancy was cost effective among populations at high risk for HIV even with HIV method efficacy ranging from 45% to 75% ( 15 ).…”
Section: Three Drivers + a Mpt For Hiv And Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…In both scenarios above–either attracting new users or expanding coverage to those with unmet need for a second indication–additional benefit is realized so long as the added coverage occurs among women at high risk for the outcomes as suggested by cost effectiveness modeling. Analyses scaling a MPT for HIV and pregnancy found pregnancy prevention would be cost effective if rolled out to women at high risk of HIV (e.g., serodiscordant couples, AGYW or female sex workers) but not to a general population of women ( 14 , 15 ). Notable was that a MPT for HIV and pregnancy was cost effective among populations at high risk for HIV even with HIV method efficacy ranging from 45% to 75% ( 15 ).…”
Section: Three Drivers + a Mpt For Hiv And Pregnancymentioning
confidence: 99%
“…Notable was that a MPT for HIV and pregnancy was cost effective among populations at high risk for HIV even with HIV method efficacy ranging from 45% to 75% ( 15 ). Modeling of the dual prevention pill (DPP) found that scaling the DPP was sensitive to both risk of HIV in the population and adherence (e.g., use-effectiveness), where if adherence was low, the health risks from unintended pregnancy could outweigh the health benefit of HIV prevention ( 14 ).…”
Section: Three Drivers + a Mpt For Hiv And Pregnancymentioning
confidence: 99%
See 1 more Smart Citation